A new finite element model of buried steel pipelines crossing strike-slip faults considering equivalent boundary springs. (15th September 2016) - Zhang, Lisong; Zhao, Xinbo; Yan, Xiangzhen; Yang, Xiujuan
Highlights: A new FEM with boundary springs for pipelines under strike-slip faults is proposed. The results of the proposed model agree well with those of the referred model. The effects of parameters on mechanical behaviors of pipelines are investigated. Abstract: A new finite element model considering equivalent boundary springs was proposed to analyze the displacement and strain of the pipeline under strike-slip faults. The purpose of introducing equivalent boundary springs was to simulate the interaction of the pipeline-soil more sufficiently, because the dimension of current models was far smaller than the actual one of the interaction of the pipeline-soil. Subsequently, a closed-form solution was derived to obtain the stiffness coefficient of equivalent boundary springs. Besides, a contact model was used in the new finite element model. The proposed model was verified through the comparison of the obtained solutions to the results of a referred model with an exact solution, with minor deviations which do not exceed about 4.34%. Meanwhile, the effects of fault displacements, kinetic friction coefficients, fault slip modes and constraint conditions of pipeline ends on the displacement and strain of pipelines were investigated. The results show that local buckling occurs more easily under smaller fault displacements, while the tensile failure tends to occur under larger fault displacements. Also, larger kinetic friction coefficients are beneficial for pipeline safety, and constraint conditions of pipeline ends have a large effect on the displacement and strain of pipelines.